Método de apoio a tomada de decisão na remediação sustentável de áreas contaminadas - Braun, Adeli Beatriz (2021)
The application of sustainability concepts in remediation processes is a recent but significant evolution in the traditional approach to managing contaminated sites. In recent years, many advances have been made in the field of sustainable remediation, however, there are still great difficulties for its application in practice, largely due to the lack of regulatory mandates, standards and more holistic methodologies that integrate a transparent guidance system to prepare and implement a sustainable remediation process. Thus, the aim was to outline a method to support decision making for the application of sustainable remediation in the management of contaminated sites. To achieve the aim, the scope of the research was divided into three main stages: 1) a list of 63 indicators was developed, divided into environmental (25), social (24) and economic (14), which can be used to qualitatively or quantitatively assess the sustainable performance of remediation techniques. These indicators were validated and weighted by 57 stakeholders from the area and from eleven different countries, confirming the relevance and applicability of the results obtained and allowing to better understand the different perceptions about sustainable remediation; 2) matrices were elaborated and structured for the screening of remediation techniques based on parameters of the contaminated site. The matrices were composed of 14 different contaminated soil remediation techniques, in addition to excavation/disposal, characterizing them in relation to 16 different input variables divided into four large groups: characteristics of soil, contamination, operation and feasibility. As a validation strategy for these matrices, they were applied in two case studies (I - international and II - national), resulting in the extraction of appropriate techniques for application in these sites and subsequent sustainability assessment (case study I - phytoremediation, electrokinetics and excavation/disposition; case study II - nanoremediation and soil washing); 3) finally, the central tool for assessing the sustainability of remediation techniques was created. The tool was designed by adapting traditional impact assessment matrices and a mathematical model for sustainability calculating. In this process, the indicators developed in the first stage were used. Validation occurred through the application of the tool to assess the sustainability of the remediation techniques selected in the previous stage (phytoremediation > electrokinetics > excavation/disposition; nanoremediation > soil flushing). The tool offers comprehensive assessments of the positive and negative impacts on the three pillars of sustainability and a diagnosis of the main impact components that influence the achievement of sustainable results from each remediation technique. In general, it is possible to highlight that the results obtained give consistency to the study and indicate its relevance, in addition to confirming the potential of the method developed to support users in decision making for the sustainable remediation application. It was also concluded that the structuring of the method in a process with sequential and complementary steps and guidelines, without the need to use complex computational tools, provides significant benefits for future users, especially when the focus is on time optimization, thus encouraging the selection and application of remediation techniques based on the principles of sustainability.